Analytic Review on Theory of Living Hadith - Nawir Yuslem; Sulidar Sulidar; Ahmad Faisal (Budapest International Research and Critics University, 2020)
This study aims to review the theory of living hadith. Every time there must be a variety of science, art and views. Every pious at the present time the birth of a number of thoughts, schools of thought, views and knowledge in various sharia magazines, history, politics, economics, social and others. The majority of these sciences are sourced from non-Muslims, and do not rely on religious scales. The theory of living hadith is now open, because there are no restrictions, no conditions for commentators or syāriḥ al-ṣadīṣ. Any interpretation by anyone is considered valid. The interpreter in this case is free to anyone without the conditions of the interpreter and without signs, including all verses and Hadith, including verses and traditions about faith and worship. This view, value-free and contextual without limits will exceed the value of faith.